1976
DOI: 10.1002/pol.1976.170140921
|View full text |Cite
|
Sign up to set email alerts
|

A note on linear calibration curve for gel‐permeation chromatography developed from a single standard

Abstract: With the increased use of high-speed gel-permeation chromatographs (GPC) interfaced with mini-computers for quick communication of results, it is desirable to use a rapid reliable method of calibration. Consider a set of columns with an appropriate distribution of pores over the desired range such that the calibration curve may be described aswhere V is the elution count, C1 and C2 are constants, and M is the molecular weight. If we have a standard polymer with a broad distribution of molecular weights over th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1981
1981
1998
1998

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…From SEC measurements, we can obtain the elution curve C(V) versus A typical unnormalized intensity-intensity photoelectron count autocorrelation function. Epoxy polymer sample 13 (1.11 X 10"4 g/mL; Afw = 4.97 X 106) in MEK measured at = 30°and 25 ®C using a delay time increment = 15 #is. The insert is relative deviation of the measured and the computed time correlation function using the MSVD method.…”
Section: Sec Calibrationmentioning
confidence: 99%
See 2 more Smart Citations
“…From SEC measurements, we can obtain the elution curve C(V) versus A typical unnormalized intensity-intensity photoelectron count autocorrelation function. Epoxy polymer sample 13 (1.11 X 10"4 g/mL; Afw = 4.97 X 106) in MEK measured at = 30°and 25 ®C using a delay time increment = 15 #is. The insert is relative deviation of the measured and the computed time correlation function using the MSVD method.…”
Section: Sec Calibrationmentioning
confidence: 99%
“…After obtaining (V), (V2), (log (D0°)>, and (log2 (D00)), we can combine them with eq 13 and 14 to solve for A and B. We also know that Mw can be calculated from SEC data by using f "MC(V) dV Mw = ^4- (15) f C(V) dV Jo if we know A and B in eq 10. By using D0°= fej>M_aD, A, and B, we can change eq 15 to jfeDl/«c r"io(A-V)/(aDB)C(y) dy Mw =--- (16) f°C(V) dV…”
Section: Sec Calibrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Many attempts have been undertaken to overcome the problem of the lack of suitable standards for each polymer type (5)(6)(7)(8)(9). These attempts employ a known set of molecular weight averages of broad molecular weight distribution polymers concerned.…”
mentioning
confidence: 99%
“…For two independent determinations (subscripts i and j ) , it can easily be shown that However, for most applications, Dz,i = D2,,; for small changes in D2,, such that D2,, 9 AD2,,, it follows, therefore, that the functional form In ( P/Pi ) = Const. (D2 -Dzi (11) results. This is consistent with the results from our empirical observations.…”
Section: Case I: the Gaussian ( Pseudo-flory ) Distributionmentioning
confidence: 99%